Assessment Of Heavy Metal Pollution Within Downstream Of Perak River Basin Using Qual2k Modelling - Roslan, Nur Aina Mohd (Universiti Sains Malaysia, 2021)
This research study has been conducted to assess status of the water quality based on the selected physio-chemical parameters as well as the concentration of heavy metals in order to understand the present scenario of water quality of the downstream of Perak River. Four tests were conducted to assess the water quality, which are Total Suspended Solid (TSS), turbidity, Total Kjeldahl Nitrogen (TKN) and heavy metals by ICP-OES. The total suspended solid (TSS), turbidity, and total kjedahl nitrogen (TKN) of tested water samples is in the range of 30.67 to 742 mg/L, 21.55 to 87 NTU and 0 to 4.928 mg/L respectively. The concentration of 19 heavy metals have been analysed using Inductively Coupled Plasma-Optical Emission Spectrometer (ICP-OES) machine. The concentration of heavy metals were in the order of Ca > Mg > Cu > Fe > Pb > Mn > Sr > V > Ti > Mo > Tl > Ni > As > Sb > Be > Co > Cr > Li > Cd. The modelling of dispersion of heavy metals along the downstream of heavy metals were made using Qual2K. Six heavy metals, which are Cd, Cu, Fe, Mn, Ni, and Pb, have been chosen as the parameters for Total Maximum Daily Load (TMDL) calculation. From the calculation of TMDL, load pollution reduction was observed to meet the targeted water quality standard for all chosen heavy metals. The value of TMDL obtained from the analysis was 1.8533 kg/day.